(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: This study aimed to evaluate the knowledge, practice, and some related factors to health professionals’ use of personal protective equipment (PPE) in the prevention of COVID-19 while engaging in medical examination, treatment, and epidemic control in the community or clinics located in the Nam Tu Liem District of Hanoi. Subject and method: Between February 2022 and March 2022, a cross-sectional descriptive study of 99 health professionals engaged in medical examination, treatment, and prevention of outbreaks in the community or the departments and medical stations of Nam Tu Liem District Medical Center was carried out. Results: The study’s findings indicated that 91.9% and 66.7% of medical personnel were adequately knowledgeable and practiced using PPE to prevent COVID-19. There was a statistically significant difference between healthcare personnel’s general knowledge and the actual use of PPE for COVID-19 prophylaxis. Conclusion: Healthcare staff must receive improved continuing training on the use of PPE in order to safeguard everyone’s safety in general and the safety of health workers in particular during the transmission disease pandemics.